Molecular characterization of the promoter region of the Brain Derived Neurotrophic Factor (BDNF) gene; Towards its involvement in academic stress induced oxidative stress and blood indices alteration in medical students - Atif, Amin Baig; Ahmad Zubaidi, A.latif; Nordin, Simbak; Tengku Mohammad Ariff, Raja Hussin (2017)
The brain derived neurotrophic factor (BDNF) gene at 11p14.1 encodes the BDNF protein which is found in the brain and spinal cord. This protein is a member of the neurotrophic family of neurotrophic factors, and one of the most important proteins, promoting the survival of neurons via regulation of the growth and maintenance of neurons. The BDNF protein plays a significant role in neurogenesis, memory and learning, mood changes, and found in regions of the brain that control drinking, eating, and body weight. It has been postulated to be involved in academic stress in medical students and alteration of blood indices as per level of oxidative stress as per academic stress. This study aimed to perform molecular characterization of the human BDNF promoter region.The sequence of the promoter region of the human BDNF(Accession no.KX964617) was obtained from Gene bank. The open reading frames (ORFs), restrictions/methylation sites against a total of 560 recognition sequences, a total of three TATA boxes (TATA, tata, Goldberg Hogness Sequences) were identified using clustal X feature of VectorNTI. Transcriptional factors binding sites (TFBS) were identified using online tool. Promoter prediction was determined by doing manually matching of TFBS with TATA box from outward in. These manual findings were compared with online promoter prediction results. A total of 11 ORFs were identified, with a total of 7 on direct strand (Table 1). A total of two vital restrictions sites; ApaLI (-479bp) and PstI (-220 bp) were found (Figure 1). Six TATA boxes [1 TATA (TATAA): at -605 bp (100.0% similar) on complementary strand, 1 tata (TTGACA): at -79 bp (100.0% similar), and 4 Goldberg–Hogness (TATAAAA): at -650 bp (85.7% similarities) on complementary, -621 bp (85.7% similarities), -530 bp (85.7% similarities), and -514 bp (85.7% similarities) on complementary] were identified (Figure 2). Sixty three TFBS were found online, four TFBS (TFIID, GR-beta, HOXD9, and HOXD10) matches exactly with Goldberg–Hogness TATA box at position -530 bp. In the online promoter prediction, prediction transcription start site (TSS) was at 300 bp.This is the first study characterizing the molecular motifs and crucial elements within the reported promoter region of BDNF though successfully characterized in this study, there is a serious need to study the involvement of these motif in the transcriptional regulation of BDNF in future studies as per the role of these transcriptional factors in academic stress in medical students and oxidative stress beside involvement in blood haemostasis.